2019
DOI: 10.1111/cogs.12703
|View full text |Cite
|
Sign up to set email alerts
|

The Minds of God(s) and Humans: Differences in Mind Perception in Fiji and North America

Abstract: Previous research suggests that how people conceive of minds depends on the culture in which they live, both in determining how they interact with other human minds and how they infer the unseen minds of gods. We use exploratory factor analysis to compare how people from different societies with distinct models of human minds and different religious traditions perceive the minds of humans and gods. In two North American samples (American adults, N = 186; Canadian students, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…These studies suggested that although it is essential to consider socio economic factors as confounders, ethnic identity has significant associations with mental health. Willard and McNamara had observed this significant association through their study and concluded that Fijians of Indian descent tend to focus more on internal mental states than Itaukei Fijians ( 32 ). This may potentially explain the significant difference of psychological wellness between the two ethnic groups.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These studies suggested that although it is essential to consider socio economic factors as confounders, ethnic identity has significant associations with mental health. Willard and McNamara had observed this significant association through their study and concluded that Fijians of Indian descent tend to focus more on internal mental states than Itaukei Fijians ( 32 ). This may potentially explain the significant difference of psychological wellness between the two ethnic groups.…”
Section: Discussionmentioning
confidence: 92%
“…As results indicated, religion is considered sacred and important to Itaukei people. Literature also indicates this, stating that Christianity is considered core aspect of identity ( 32 ). This may potentially explain results of Itaukei participants having higher scores for spiritual wellness.…”
Section: Discussionmentioning
confidence: 96%
“…Cross-cultural variation in conceptions of the mind may also shape the extent to which people engage in mentalizing across contexts (Willard and McNamara 2019). Anthropologists have identified six different "theories of mind" from across the ethnographic spectrum.…”
Section: Mentalizingmentioning
confidence: 99%
“…The majority of the cognition themes related to religious and cultural influences on attitudes and beliefs. For example, Willard and McNamara [45] found Fijians' conceptualisation of the human mind, the agentic self and the nature of God was more socio-centric and multivariate than North American samples, despite similar Christian religious teachings about God. This finding indicate the collectivist cultural influence not just on social behaviours and values but also on central aspects of one's consciousness and sense of agency.…”
Section: Cognition and Social Behaviormentioning
confidence: 99%